1980
DOI: 10.1007/bf00441582
|View full text |Cite
|
Sign up to set email alerts
|

Histological findings in testes with varicocele during childhood and their therapeutic consequences

Abstract: Contrary to widespread opinion, varicocele is a common disorder in children and can be seen in 10-year-old boys. The peak incidence of varicocele is reached at 15 years. Usually the disorder remains asymptomatic and is overlooked. Over 5 years we observed 22 boys with varicocele. Testicular biopsy carried out in 10 of them demonstrated essentially the same changes of tubules, interstitium and blood vessels seen in adults, though in a less severe form. Surgical removal of varicocele should therefore be carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(32 citation statements)
references
References 15 publications
4
25
0
3
Order By: Relevance
“…This improvement in low level of LH is consistent with the impairment of Leydig cell ultrastructure observed in testicular biopsy samples in some patients with a varicocele, and Leydig cell function in rats with experimental varicoceles [19].…”
Section: A K H Younessupporting
confidence: 85%
See 1 more Smart Citation
“…This improvement in low level of LH is consistent with the impairment of Leydig cell ultrastructure observed in testicular biopsy samples in some patients with a varicocele, and Leydig cell function in rats with experimental varicoceles [19].…”
Section: A K H Younessupporting
confidence: 85%
“…Patients with varicocele have altered levels of serum inhibin, which is produced by Sertoli cells [32]. In addition, histologic studies of testicular biopsies from patients with varicoceles have demonstrated that germ cells in the adluminal compartment of the seminiferous tubules are sloughed off, a sign often associated with compromised Sertoli cell function [12,19]. These studies suggest that insufficient endocrine support of Sertoli cell function may compromise spermatogenesis in the varicocele testis.…”
Section: A K H Younesmentioning
confidence: 99%
“…Reduction in the volume of the ipsilateral testicle [16,22] as well as histological alterations similar to those observed in the adult male with varicocele have been reported in boys with varicocele [6,7]; therefore, early surgery for varicocele has been recommended to prevent further alterations of the testicular functions [2,10,11].…”
Section: Discussionmentioning
confidence: 69%
“…37 In humans, the presence of a varicocele leads to elevated temperature of the testicle and impaired spermatogenesis. 38,39 Hypoxia In rats, the expression of hypoxia inducible factor is elevated in the presence of a varicocele and subsequently decreases with repair. 40,41 It is postulated that stasis of blood could affect partial oxygen pressure and metabolism in the testis.…”
Section: Proposed Mechanism Detailsmentioning
confidence: 99%